2014
DOI: 10.1080/21639159.2014.881114
|View full text |Cite
|
Sign up to set email alerts
|

The impact of natural disasters on the values and lifestyles of consumers: in the case of the Tohoku Earthquake

Abstract: This study focuses on the values constituting a Lifestyles of Health and Sustainability (LOHAS)-oriented lifestyle. It reveals how the Tohoku Earthquake affected the lifestyles and consumption behaviors of consumers. The study consists of two substudies. In Study 1, the values constituting a LOHAS-oriented lifestyle are specified. Additionally, the manner in which those values change is shown based on a statistical analysis of consumer survey data collected at five points in time. In Study 2, lifestyles are cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Changes in consumer behavior emerge because of individuals' adjustments to the personally experienced adverse impacts of the disaster. Nishio et al (2014) observed that after the Tohoku earthquake in Japan, the importance of environmental values had decreased among people. The present study draws a similar but much more precise conclusion: It found that sustainable consumption and sustainable consumption consciousness have declined in many facets (ecological, social and voluntary simplicity) because of the pandemic.…”
Section: The Covid-19 Pandemic As a Natural Disastermentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in consumer behavior emerge because of individuals' adjustments to the personally experienced adverse impacts of the disaster. Nishio et al (2014) observed that after the Tohoku earthquake in Japan, the importance of environmental values had decreased among people. The present study draws a similar but much more precise conclusion: It found that sustainable consumption and sustainable consumption consciousness have declined in many facets (ecological, social and voluntary simplicity) because of the pandemic.…”
Section: The Covid-19 Pandemic As a Natural Disastermentioning
confidence: 99%
“…Based on research on the impacts of natural disasters (e.g., Forbes, 2017; Larson & Shin, 2018; Nishio et al, 2014; Sneath et al, 2009) and the COVID‐19 pandemic (e.g., Cohen, 2020; Mathios et al, 2020; Tonne, 2020), there are arguments for a positive impact (“window of opportunity”) of the pandemic on sustainable consumption and personal well‐being as well as for an opposite effect (“time of turning away”). Considering the scenario of a “window of opportunity” for sustainable consumption, theoretical perspectives have suggested a positive effect of the coronavirus pandemic on sustainable consumption patterns (e.g., Cohen, 2020; Mathios et al, 2020; Tonne, 2020).…”
Section: Hypotheses and Research Questionmentioning
confidence: 99%